RETHINKING TERRITORY DEVELOPMENT IN GLOBAL COMPARATIVE RESEARCHES - Boronenko, Vera; Lonska, Jelena (European Scientific Journal, ESJ, 2014)
From previous international research experience of the authors, they have a sense that Economics of Development, as well as the global ratings make a systemic error, losing sight of the fact that in a global space, there are different types of territory development (TD). It is time to shift the focus from how much the economy produces, to what it produces, and why. Based on the data of GCR, the authors offer an alternative Global Rating of TD, which compares a country not with other one, but with itself during some period of time. First attempts of the economic theory in rethinking TD were made by F.Braudel in 1967, who argued that the worldâ€™s economic history is presented as an alternation of dominance of autonomous regions â€” world-economies. In their research authors were checking the hypothesis within pluralistic (qualitative) paradigm of TD: there are many types (qualities) of TD in the world, many self-reliant â€œdevelopmentsâ€, not a single quantitative path of development as it is within evolutionary (quantitative) paradigm. The practical result of this research is the idea that so-called â€œdevelopedâ€ countries of the world are not so developed, al least because of their low growth capacity, but so-called â€œunderdevelopedâ€ countries in general have just another type (quality) of development.